Chemical, optical and photovoltaic properties of TiO2/reduced graphene oxide photoanodes sensitized with Roselle and N719 dyes for dye-sensitized solar cell application. Issue 4 (8th April 2020) - Omar, Azimah; Fakir, Muhamad Saipul; Hamdan, Khairus Syifa; Rased, Nurul Hidayah; Rahim, Nasrudin Abd.
Abstract : Purpose: The purpose of this paper is to investigate the chemical, optical and photovoltaic properties of titanium dioxide/reduced graphene oxide (TiO2 /rGO) photoanodes immersed in natural Roselle and synthetic (N719) dyes for dye-sensitized solar cell (DSSC) application. Design/methodology/approach: TiO2 mixed with rGO were doctor-bladed on fluorine doped tin oxide (FTO) glass substrate. The chemical and optical properties of TiO2 /rGO photoanodes immersed in Roselle and N719 dyes were characterized using Fourier-transformed infrared (FTIR) and ultraviolet–visible (UV–vis) spectroscopies, respectively. The DSSC's photovoltaic performances were tested using Visiontec Solar I-V tester at standard illumination of AM1.5 and irradiance level of 100 mW/cm 2 . Findings: The presence of anthocyanin dye from Roselle flower was detected at 604 nm and 718 nm. TiO2 /rGO+Roselle dye sample revealed the smallest energy gap of 0.17 eV for ease of electron movement from valence band to conduction band. The TiO2 /rGO-based DSSC fabricated with Roselle dye had a power conversion efficiency, ƞ of 0.743 per cent higher than TiO2 /rGO photoanode sensitized with N719 dye (0.334 per cent). The obtained J-V curves were analyzed by a single-diode model of Lambert W-function and manual optimization to determine the internal electrical parameters of the DSSC. The average and uncertainty values of Jsc and ƞ were evaluated at different Rsh range of 1362 Ω to 32 k Ω. Research limitations/implications: Rs values were kept constant during optimization work. Originality/value: New ideality factor of TiO2 /rGO-based DSSC was re-determined around 0.9995.